Psychological factors shaping public acceptance of the adoption of autonomous vehicles in Indonesia - Sitinjak, Charli; Simic, Vladimir; Pamucar, Dragan * (Elsevier, 2024)
Introduction The rapid development of autonomous vehicles (AVs) has the potential to revolutionize transportation systems and address societal challenges. However, understanding the psychological factors influencing public acceptance and readiness for AV adoption is crucial for successful implementation. This study provides a comprehensive analysis of these psychological factors, specifically focusing on the context of health issues in Indonesia.